Investigating of the Relationship between Job Satisfaction and Organizational Commitment Case Study; Professors and Administrative Staff of the Logar University - Tahir Khaplwak, Muhammad; Mommand, Abdul Azim; Abdulrahimzai, Wahidullah (International Journal of Scientific Research and Management (IJSRM), 2020)
Job satisfaction and organizational commitment that play a very important role in the growth and survival of organizations and reduce delays and layoffs of employees and increase the level of efficiency and effectiveness in organizations. The study, entitled “Investigating the Relationship between Job Satisfaction and Organizational Commitment from the Perspective of Professors and Administrative Staff of the Logar University” is a descriptive-correlational study. Its main purpose was to study the relationship between job satisfaction and organizational commitment. The statistical population is the professors and staff of the University of Logar University. Due to the small number of professors and staff of this institution, all of them (30) have been included in the research. In this study, the required information was collected by two questionnaires of job satisfaction and organizational commitment and was analyzed using SPSS24 and EXCEL software and its descriptive and inferential results are described in the tables, which in the descriptive method describes the variables of satisfaction. Job (nature of work, co-workers, growth opportunities and payments) and organizational commitment variables (emotional commitment, continuous commitment and normative commitment) and in inferential analysis by correlation test or Pearson correlation to test hypotheses and analyze the relationship between Job satisfaction J and organizational commitment are addressed. The results of the research show that the majority of the employees of this institution are satisfied with their work; but they are not satisfied with the behavior and attitude of the supervisors. On the contrary, the majority of the employees of this institution read the behavior of their colleagues as friendly and satisfied. The majority of the employees of this organization have said that there is no suitable opportunity for growth and promotion. The majorities of the employees of this institution are interested in this organization and consider the problems of the organization as their problems; but they do not see the current organization as suitable for securing their future, and they will leave the organization if they are offered a better job elsewhere. The results showed that the majority of the faculty and staff of this organization are below the level of job satisfaction (supervisors, growth opportunities and payments) and are below the level of continuous commitment.Regarding the hypotheses, the research showed that there is no relationship between the nature of work and emotional commitment. There is a significant relationship between the behavior of supervisors and normative commitment. There is no significant relationship between employee behavior and normative commitment. There is a significant and positive relationship between growth opportunities and pay and continuous commitment. There is a positive and significant relationship between job satisfaction and organizational commitment of the professors and staff of the Logar University.